2018
DOI: 10.1017/s0014479718000212
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Irrigated and Rain-Fed Rice (Oryza Sativa) Producers in Fadama Agriculture, Nigeria

Abstract: SUMMARYGiven the importance of irrigation for rice production, this study compared the technical efficiency of irrigated and rain-fed rice (Oryza sativa) farms in the Upper Niger River Basin and Rural Development Authority (UNRBDA), Nigeria. Primary data were collected from 300 irrigators and 325 rain-fed rice producers. Applying the stochastic frontier Cobb–Douglas production function, net income analysis and Likert scale rating techniques, the study found that irrigated scheme increased marginal factor produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
(24 reference statements)
4
9
0
Order By: Relevance
“…To boost rice output, the rice producers should lower the amount of fertilizer used. The results are consistent with Opata et al (2019) and Kadiri et al (2014) also contradict the finding of Biam et al (2016) and Nimoh et al (2012). Also, the RUE values for labour and agrochemicals are both < unity, 0.0354 and 0.00473, respectively.…”
Section: Resource-use Efficiency (Rue)supporting
confidence: 83%
See 3 more Smart Citations
“…To boost rice output, the rice producers should lower the amount of fertilizer used. The results are consistent with Opata et al (2019) and Kadiri et al (2014) also contradict the finding of Biam et al (2016) and Nimoh et al (2012). Also, the RUE values for labour and agrochemicals are both < unity, 0.0354 and 0.00473, respectively.…”
Section: Resource-use Efficiency (Rue)supporting
confidence: 83%
“…The majority of rice farmers (74%) were members of a cooperative association, while the remaining 26% were not. Farmers that join cooperatives have the opportunity to share information on modern agricultural technologies and to benefit from agricultural business advice and group marketing, resource pooling, and profit maximization (Opata et al, 2019). The majority of farmers (84%) had no access to credit to finance their rice-producing activities, whereas only 16% had access to credit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Babatunde et al [33] examined the determinants of yield gap and technical efficiency between rain-fed and irrigated rice production in Nigeria, and found that irrigated rice producers were 11% more technically efficient than rain-fed farmers. Opata et al [34] also found that irrigators were 38% more technically efficient than rain-fed farmers in rice production in Nigeria. Mkanthama et al [35] found a great difference in technical efficiency in rice production in Tanzania, where technical efficiency was 96% for irrigators compared to 39% for rain-fed farmers.…”
Section: Introductionmentioning
confidence: 95%